A single switcher combined series parallel hybrid envelope tracking amplifier for wideband RF power amplifier applications - Harmanani, Haidar (2017)
In this paper, an improved architecture for RF power amplifier envelope tracking supply modulator is presented. It consists of a single switched mode supply regulator and one linear regulator. The switched mode supply regulator has two outputs, one of which is used in conjunction with the linear regulator to provide a wideband, high efficiency power supply to the RF amplifier, whereas the second output provides a band limited high efficiency supply to the linear regulator. The design offers improved power efficiency, reduced system complexity and area savings since the dual output switched mode regulator requires one inductor and a simple control loop. The design was implemented in 14nm CMOS process and validated with simulations. The supply modulator achieves a peak efficiency of 74% with a 6 dB PAPR 20MHz LTE signal at 29dBm output power.